2008
DOI: 10.1007/s00417-007-0763-6
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response relationship in inferior oblique muscle recession

Abstract: Despite the large variation of effects, a dose-response relationship could be established, facilitating surgical planning. Large vertical deviations with small excyclodeviation are an indication for additional anteropositioning. The torsional effect of inferior oblique muscle recessions can diminish over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…The dose–effect relationship after 6 months for an accommodative near target at 25° adduction was 0.83° ± 0.43° per mm of recession. This value is within the confidence interval of studies using a similar recession technique [ 17 ]. Six months postoperatively, only a minimal cicatrisation was found along the openings, which did not hinder free movement of the conjunctiva over the sclera and muscle.…”
Section: Discussionsupporting
confidence: 78%
“…The dose–effect relationship after 6 months for an accommodative near target at 25° adduction was 0.83° ± 0.43° per mm of recession. This value is within the confidence interval of studies using a similar recession technique [ 17 ]. Six months postoperatively, only a minimal cicatrisation was found along the openings, which did not hinder free movement of the conjunctiva over the sclera and muscle.…”
Section: Discussionsupporting
confidence: 78%
“…Mataftsi [27] studied time-related changes after IO weakening in SO palsy, and reported that the corrective amount of vertical and cyclotorsion in the primary position had a tendency to increase at 4 months or longer compared with that within 7 days after surgery. Metten [28] also describes a slight increase in the corrective effect on the primary position after 3 months postoperatively. However, our results show that the corrective effects in the case group did not significantly vary during the observation period.…”
Section: Discussionmentioning
confidence: 93%
“…Morad et al [30] reported the mean preoperative central gaze hypertropia of 12.5±6.2 PD had an average correction of 9.1 PD for central gaze and 15.4 PD for contralateral gaze after 10 mm IOR. Metten et al [31] reported dose-response that each mm of IO recession corrects 0.5° (0.5°/mm) in the central position, and up to 1.4° (1.4°/mm) in adduction. Yanyali [32] reported that mean reduction in hypertropia in primary gaze was 18.5 PD in eyes underwent IO anterior transposition, compared to 13.…”
Section: Treatment Of Strabismus Secondary To Trochlear Nerve Palsymentioning
confidence: 99%